2012
DOI: 10.1016/j.eplepsyres.2012.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Variability of sclerosis along the longitudinal hippocampal axis in epilepsy: A post mortem study

Abstract: SummaryDetailed neuropathological studies of the extent of hippocampal sclerosis (HS) in epilepsy along the longitudinal axis of the hippocampus are lacking. Neuroimaging studies of patients with temporal lobe epilepsy support that sclerosis is not always localised. The extent of HS is of relevance to surgical planning and poor outcomes may relate to residual HS in the posterior remnant. In 10 post mortems from patients with long histories of drug refractory epilepsy and 3 controls we systematically sampled th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 53 publications
2
34
2
1
Order By: Relevance
“…Finally, the observed association between distinct hippocampal recruitment patterns and different seizure phenotypes may provide an explanation for the heterogeneity of seizure types seen in patients who exhibit diverse patterns of hippocampal pathology (Forsgren et al, 1996; Thom et al, 2012). For example, we found that a strong negative BOLD response was evoked in the contralateral dentate gyrus during high frequency DH, but not IH, stimulation.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, the observed association between distinct hippocampal recruitment patterns and different seizure phenotypes may provide an explanation for the heterogeneity of seizure types seen in patients who exhibit diverse patterns of hippocampal pathology (Forsgren et al, 1996; Thom et al, 2012). For example, we found that a strong negative BOLD response was evoked in the contralateral dentate gyrus during high frequency DH, but not IH, stimulation.…”
Section: Discussionmentioning
confidence: 94%
“…However, a correlation between the loss of pyramidal cells and the loss of interneurons in the hilus and in CA1 has also been shown in human TLE (Thom et al, 2012). In addition, that study showed that gradients of cell loss of principal cells and interneurons occur along the human longitudinal hippocampal axis in TLE with a trend toward stronger loss in the anterior and intermediate hippocampus.…”
Section: Discussionmentioning
confidence: 96%
“…Neurogenesis, together with the reduction of inhibitory interneurons in this region, might comprise a network with disturbed excitation-inhibition balance and high epileptogenicity. The functional consequences of such gradual changes might be transferred to human TLE in which gradients of cell loss along the longitudinal hippocampal axis have been shown (Thom et al, 2012). In addition, our precise quantitative analysis of interneuron densities and neurogenesis in the whole hippocampus paves a way for modeling studies on the epileptogenicity of small shifts in network balance.…”
Section: Discussionmentioning
confidence: 99%
“…At a lower titer, TMEV inoculation was not associated with complete sclerosis of CA1, or hippocampal atrophy to the extent described herein. The observed pathological consequences of high-titer TMEV infection, namely complete, bilateral sclerosis of CA1, relates to human post-mortem analyses describing bilateral or symmetrical sclerosis in hippocampi from patients with epilepsy (Thom et al, 2012) and in mixed autopsy samples with hippocampal sclerosis (Zarow et al, 2012). Further, a large proportion of autopsies containing hippocampal sclerosis match criteria for complete sclerosis of CA1 (Zarow et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular and molecular insight is needed to better define relationships between behavioral changes and the neuropathology often observed in epilepsy. In the case of TLE, special emphasis has been placed on hippocampal pathology like sclerosis, mossy fiber sprouting, granule cell dispersion, and gray matter loss (Thom et al, 2012, Kandratavicius et al, 2013, Winston et al, 2013). …”
Section: Introductionmentioning
confidence: 99%